The Role and Necessity of the Development of Small Business and Entrepreneurship Based on Foreign Investments - Djulmatova S.R. (Mathematical Statistician and Engineering Applications, 2023)
The development of the modern economy is impossible without an initiative policy to support small businesses and private entrepreneurship. World experience shows that small business is an important element of a market economy, without which a country cannot develop harmoniously. This article describes ways to develop small business and entrepreneurship through foreign investment.